Bleeding in patients with continuous-flow left ventricular assist devices: acquired von Willebrand disease or antithrombotics?. (31st October 2021) - Consolo, Filippo; Marasi, Alessandra; Della Valle, Patrizia; Bonora, Marta; Pieri, Marina; Scandroglio, Anna Mara; Redaelli, Alberto; Zangrillo, Alberto; D'Angelo, Armando; Pappalardo, Federico
Abstract: OBJECTIVES: To evaluate the competing pro-haemorrhagic contribution of acquired von Willebrand (vW) disease and antithrombotic therapy in patients implanted with continuous-flow left ventricular assist devices (LVADs). METHODS: We compared the extent of vW factor (vWf) degradation [vWf antigen (vWf:Ag)] and a decrease of functional activity of large vWf multimers [vWf collagen binding (vWf:CB)] in LVAD patients who did and did not suffer from bleeding. Data were measured pre-implant, at short-term (t1: <3 months) and long-term (t2: >12 months) follow-up. The occurrence of primary bleeding events, as well as bleeding recurrence, was correlated with patient-specific vWf profile and antithrombotic regimen. Indeed, patients were discharged on warfarin (international normalized ratio: 2–2.5) and aspirin, with the latter withhold after a first bleeding episode. RESULTS: Fifty-three patients were enrolled. The median follow-up was 324 (226–468) days. We recorded 25 primary bleeding events (47% of patients). All primary events occurred in patients on warfarin and aspirin. Both vWf:Ag and vWf:CB decreased significantly post-implant ( P = 0.0003 and P < 0.0001), and patients showing pathological vWf:CB/vWf:Ag ratio (<0.7) increased progressively over the time of support (pre-implant = 26%, t1 = 58%, t2 = 74%; P < 0.0001). Of note, activity of large vWf multimers of bleeders was significantly lower at t2 with respect to non-bleeders (vWf:CB: 61 (36–115) vs 100 (68–121), P = 0.04; vWf:CB/vWf:Ag ratio: 0.36 (0.26–0.61) vs 0.58 (0.33–0.96), P = 0.04). Despite these marked differences in the vWf profile, following aspirin discontinuation only 3 patients had bleeding recurrence. CONCLUSIONS: Aspirin contributes significantly to haemorrhagic events in the background of acquired vW disease; its discontinuation significantly reduces bleeding recurrence. Clinical trial registration: https://clinicaltrials.gov/ct2/show/NCT03255928 ; ClinicalTrials.gov Identifier: NCT03255928. Abstract : The clinical success of left ventricular assist devices (LVADs) has grown enormously.